(untitled) (SAARC Journal of Agriculture, 2017)
Performances of tissue cultured (TC) plantlets of BARI Kola-3 and BARI Kola-4 were evaluated against transplanting of conventional (CON) sucker at hill valleys during July 2011 to December 2014. The plantlets were produced at Biotech Lab, BARI Gazipur and validation trial was conducted at Ramgarh, Khagrachari hill district during March-April and September-October planting seasons (2011-14). Murashige and Skoog (MS) basal medium supplemented @ 3 mg 1-l and 5 mg l-1 BAP showed the best performance for multiple shoot production in BARI Kola-3 and BARI Kola-4, respectively. Both the varieties produced well developed roots in ½MS medium supplemented @ 0.5 mg 1-l IBA. Among the plantlets 98.5% plantlets were survived when hardened 7 days under polyethylene tunnel after 5 days hardening at room temperature but 100% plantlets died when transplanted plantlets were kept in open conditions at the nursery. 45 day - old healthy plantlets were planted at hill valleys in September-October and April-May planting seasons. BARI Kola-3 produced the highest 45.67 and 44.05 t ha-1 bunch yield at April-May and September-October planting, respectively. The highest 55.89 t ha-1 bunch yield was recorded from TC BARI Kola-4 in March-April planting followed by 49.67 t ha-1 in September-October Planting. TC BARI Kola-3 and BARI Kola-4 produced 3.68 and 12.52% higher yields in March-April planting, respectively than September-October planting. In case of planting materials, TC BARI Kola-3 and TC BARI Kola-4 produced 23.43 and 20.33% higher yield over CON suckered plant in March-April planting. On the other hand, TC BARI Kola-3 and TC BARI Kola-4 also produced 12.34 and 9.35% higher yield than CON Suckered plant in September-October planting. Similarly, TC BARI Kola-4 produced 28.33% higher yield than CON suckered BARI Kola-4 in March-April planting. In every case, TC plants showed better performances than the CON suckered plant. SAARC J. Agri., 15(1): 67-76 (2017)